(untitled) (Development Service Industry Management, 2025)
Protected areas play a key role in ensuring the sustainable socio-economic development of society. They not only perform their main functions of preserving biodiversity and protecting the environment, but also create favorable conditions for recreation, tourism, and meeting the recreational needs of the population. Among the various forms of travel, ecotourism is becoming increasingly popular in the world. This direction is developing in both developed and developing countries, as more and more tourists seek to visit natural landscapes preserved in their pristine state. Routes that allow you to directly experience harmony with nature and learn about unique ecosystems are especially attractive. Despite this, discussions are ongoing among scientists about the possibility of achieving such a tourism model that would fully comply with the principles of the global concept of sustainable development. Practice shows that the most successful examples of ecotourism implementation are characteristic of those countries where the principles of rational nature management, active involvement of local communities and environmental education of tourists are purposefully implemented. The article considers the international experience of organizing ecological tourism in nature reserves. Based on the analysis of European and American practices, both common features and differences in organizing trips to nature reserves were identified. This allowed us to determine the features of the formation of tourist routes, approaches to natural resource management and interaction with the local population. World practice convincingly proves that ecotourism in the context of sustainable development involves: preserving nature and biodiversity, economic benefits for the region through infrastructure development and job creation, support for local communities and cultural heritage. It has been established that effective management of nature reserves is a dynamic process that combines various types of activities. Its result should be the formation of a balanced system capable of satisfying the growing recreational needs of society without harming the environment. Thus, protected areas become an inexhaustible resource for environmentally friendly tourism, which contributes simultaneously to economic growth and the preservation of natural and cultural heritage.